2017 Charlottesville Riots – Media Coverage Paper: Media & Terrorism (University of Denver Undergraduate Research Journal, 2023)
This paper intended to dissect the similarities and differences of media coverage for a very significant recent event--the 2017 Charlottesville "Unite the Right" riots and anti-racism protests.  A focal moment within this series of events is the car attack by perpetrator James Alex Fields Jr., a white-supremacist responsible for the death of one woman and countless other injuries.  The analysis reflects the coverage of this event through the lens of MSNBC and Fox News, two politically contrasting domestic news sources.  An emphasis on media framing, which is loosely how media is manipulated to make the consumer think about a certain topic in one way, helped categorize and describe the differences of these two sources.  This discussion of multiple framing variables ultimately showed that these two sources captured a single event in very different ways.  These discrepancies illuminate a significant contrast in perspectives of this violent and hateful event.